Three-Dimensional Contrast-Enhanced Magnetic Resonance Pulmonary Angiography in the Study of Pulmonary Vascular Pathology - Thomas, B (2011)
OBJECTIVES: To assess the feasibility of performing pulmonary angiography using MRI with contrast enhancement in patients with pulmonary vascular disease. METHODS: We present our experience in ten individuals, two controls and eight patients who underwent the exam after injection of a gadolinium-based contrast agent on a 1 Tesla MR scanner using a time-of-flight sequence and breath-holding during injection of contrast. RESULTS: Pathology in the main pulmonary artery and its major branches was detected easily while resolution at the segmental and subsegmental levels was inadequate. CONCLUSION: Contrast-enhanced magnetic resonance pulmonary angiography is feasible on a 1 Tesla MR scanner for the study of pathology of the main pulmonary artery and its major branches, like massive pulmonary embolism. However its ability to detect and define distal vessel pathology as found in chronic thromboembolic pulmonary hypertension and small pulmonary emboli is limited.